2.3x=162
1)tìm x bt:
a)7.2x=56
b)(2x+1)3=9.81
c)x3=82
d)4.2x-3=1
e)2.3x=162
a)7.2x=56⇔2x=8⇔2x=23⇔x=3
b)(2x+1)3=9.81⇔(2x+1)3=93⇔2x+1=9⇔2x=8⇔x=4
c)x3=82⇔x3=26⇔x=22⇔x=4
d)4.2x-3=1⇔4.2x=4⇔2x=1⇔2x=20⇔x=0
e)2.3x=162⇔3x=81⇔3x=34⇔x=4
4x+2.3x=16.125
`4^(x+2) .3^x = 16.12^5`
`4^(x+2) .3^x = 4^2 . (3.4)^5`
`4^(x+2) .3^x = 4^2 . 3^5. 4^5`
`4^(x+2) .3^x = 4^7 . 3^5`
`4^(x+2) .3^x = 4^(5+2) . 3^5`
`x=5`
Ta có:4x+2.3x=16.125
⇔ 4x+2.3x=417.315
⇔ 4x+2:417.3x:315=1
⇔ 4x-15.3x-15=1
⇔ 12x-15=120
⇔ x-15=0
⇔ x=15
Ta có: \(4^{x+2}\cdot3^x=16\cdot12^5\)
\(\Leftrightarrow4^x\cdot16\cdot3^x=16\cdot12^5\)
\(\Leftrightarrow12^x=12^5\)
hay x=5
2.3x=10.312+8.274
\(2.3^x=10.3^{12}+8.\left(3^3\right)^4\)
\(2.3^x=10.3^{12}+8.3^{12}\)
\(2.3^x=3^{12}.\left(10+8\right)\)
\(2.3^x=3^{12}.18\)
\(3^x=3^{12}.18:2\)
\(3^x=3^{12}.9\)
\(3^x=3^{12}.3^2\)
\(3^x=3^{14}\)
\(\Rightarrow x=14\)
2.3x=10.312+8.274
2.3x=10.312+23.312
2.3x=312.18
2.3x=312.32.2
2.3x=314.2
=>x=14
2.3x+3=10.312 + 8.312
\(2.3^{x+3}=10.3^{12}+8.3^{12}\)
\(\Leftrightarrow2.3^{x+3}=18.3^{12}\)
\(\Leftrightarrow3^{x+3}=9.3^{12}\)
\(\Leftrightarrow3^{x+3}=3^{14}\)
\(\Leftrightarrow x+3=14\Leftrightarrow x=11\)
\(\Leftrightarrow2\cdot3^{x+3}=3^{12}\cdot18\\ \Leftrightarrow2\cdot3^{x+3}=3^{14}\cdot2\\ \Leftrightarrow x+3=14\Leftrightarrow x=11\)
2.3x+3=10.312+8.3122.3x+3=10.312+8.312
=2.3x+3=18.312⇔2.3x+3=18.312
=3x+3=9.312⇔3x+3=9.312
=3x+3=314⇔3x+3=314
=x+3=14⇔x=11
2.3x + 5.3x + 1 = 153
\(2.3^x+5.3^x.3=153\Leftrightarrow2.3^x+15.3^x=153\)
\(\Leftrightarrow17.3^x=153\Leftrightarrow3^x=9\Leftrightarrow x=2\)
\(\Leftrightarrow2.3^x+5.3.3^x=153\)
\(\Leftrightarrow17.3^x=3^2.17\)
\(\Leftrightarrow3^x=3^2\Rightarrow x=2\)
2.3x=10.312+8.274
mình thêm nhé
2.3x=10.312+8.274
2.3x=10.312+23.312
2.3x=312.18
2.3x=312.32.2
2.3x=314.2
=>x=14
4.3x+2 − 2.3x+1 = 810
Ta có: \(4.3^{x+2}-2.3^{x+1}=810\)
\(4.3^{x+1}.3-2.3^{x+1}=810\)
\(2.3^{x+1}\left(2.3-1\right)=810\)
\(2.3^{x+1}.5=810\)
\(3^{x+1}=81=3^4\)
x+1=4
x=3
2.3x+1 = 10. 312 + 8. 312
\(2.3^{x+1}=10.3^{12}+8.3^{12}\\ VP=\left(10+8\right).3^{12}=18.3^{12}=2.3^2.3^{12}\\ =2.3^{2+12}=2.3^{14}\\ VT=VP\\ \Rightarrow2.3^{x+1}=2.3^{14}\\ \Rightarrow x+1=14\\ Vậy:x=14-1=13\)
2.3ˣ⁺¹ = 10.3¹² + 8.3¹²
2.3ˣ⁺¹ = 3¹².(10 + 8)
2.3ˣ⁺¹ = 3¹².18
3ˣ⁺¹ = 3¹².18 : 2
3ˣ⁺¹ = 3¹².9
3ˣ⁺¹ = 3¹².3²
3ˣ⁺¹ = 3¹⁴
x + 1 = 14
x = 14 - 1
x = 13
\(2\cdot3^{x+1}=10\cdot3^{12}+8\cdot3^{12}\\\Rightarrow 2\cdot3^{x+1}=3^{12}\cdot(10+8)\\\Rightarrow 2\cdot3^{x+1}=3^{12}\cdot18\\\Rightarrow 2\cdot3^{x+1}=3^{12}\cdot3^2\cdot2\\\Rightarrow 3^{x+1}=3^{12}\cdot3^2\\\Rightarrow 3^{x+1}=3^{14}\\\Rightarrow x+1=14\\\Rightarrow x=14-1\\\Rightarrow x=13\\Vậy:x=13\)
Giải bất phương trình 9 x ≤ 2 . 3 x + 3
A. 1/3 ≤ x ≤ 1
B. 1/3 ≤ x ≤ 3
C. x ≤ 1
D. -1 ≤ x ≤3
-1/2.3x+3/4=-2,25
-1/2.3x+3/4=-2.25
-1/2.3x+3/4=9/4
-1/2.3x =9/4-3/4
-1/2.3x =3/2
3x =3/2:-1/2
3x =-3
x =-3:3
x =-1
vậy x=-1
\(-\frac{1}{2}.3x+\frac{3}{4}=-2,25\)
\(\Rightarrow\frac{1}{2}.(-3).x+\frac{1}{2}.\frac{3}{2}=\frac{9}{4}\)
\(\Rightarrow\frac{1}{2}.\left(-3x+\frac{3}{2}\right)=\frac{9}{4}\)
\(\Rightarrow-3x+\frac{3}{2}=\frac{9}{4}:\frac{1}{2}\)
\(\Rightarrow-3x+\frac{3}{2}=\frac{9}{2}\)
\(\Rightarrow-3x=3\)
\(\Rightarrow x=-1\)